Overexpression of Mitogen-activated protein kinase phosphatase-3 (MKP-3) reduces FoxO1 phosphorylation in mice hypothalamus - Rodrigues, Bárbara de Almeida; Kuga, Gabriel Keine [UNESP]; Muñoz, Vitor Rosetto; Gaspar, Rafael Calais; Tavares, Mariana Rosolen; Botezelli, José Diego; da Silva, Adelino Sanchez Ramos; Cintra, Dennys Esper; de Moura, Leandro Pereira; Simabuco, Fernando Moreira; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Elsevier, 2017)
The mitogen-activated kinase phosphatase-3 (MKP-3) has gained great importance in the scientific community by acting as a regulator of the cell cycle through dephosphorylation of FoxO1, an important transcription factor involved in the insulin intracellular signaling cascade. When dephosphorylated and translocated to the nuclei, FoxO1 can promote the transcription of orexigenic neuropeptides (NPY/AgRP) in the hypothalamus, whereas insulin signaling is responsible for the disruption of this process. However, it is not understood if the hypothalamic activation of MKP-3 affects FoxO1 phosphorylation, and we hypothesized that MKP-3 overexpression reduces the capacity of the insulin signal to phosphorylate FoxO1. In the present study, we overexpressed the DUSP6 gene through an injection of adenovirus directly into the hypothalamic third ventricle of Swiss mice. The colocalization of the adenovirus was confirmed by the immunofluorescence assay. Then, MKP-3 overexpression resulted in a significant reduction of hypothalamic FoxO1 phosphorylation after insulin stimulation. This effect was independent of changes in Akt phosphorylation. Thus, the role of MKP-3 in the hypothalamus is closely associated with FoxO1 dephosphorylation and may provide a potential therapeutic target against hypothalamic disorders related to obesity and unbalanced food intake control.
Keywords: Hypothalamus; Insulin; MKP-3